The role of neuroimaging in Alzheimer’s disease: implications for the diagnosis, monitoring disease progression, and treatment - Julius Mulumba; Rui Duan; Bo Luo; Jiang Wu; Muhammad Sulaiman; Feng Wang; Yong Yang (Exploration of Neuroscience)
Alzheimer’s disease (AD) is a neurodegenerative disorder that affects millions of people worldwide. It presents a significant challenge in terms of accurate diagnosis, disease progression monitoring, and the development of effective treatments. This article addresses the role of neuroimaging as an advancing tool for diagnosis, monitoring progression, and treatment of AD. A comprehensive review of existing literature on the use of neuroimaging in AD was conducted using various databases. The different imaging techniques, such as magnetic resonance imaging (MRI), single photon emission computed tomography (SPECT), and positron emission tomography (PET), were examined in terms of their ability to detect amyloid beta (Aβ) plaques and neurofibrillary tangles (NFTs), the hallmark pathological features of AD. Neuroimaging enables the visualization of Alzheimer-related biomarkers, such as Aβ plaques, tau protein tangles, neuro-inflammation, and synaptic dysfunction, providing valuable insights into disease pathophysiology and progression. These imaging techniques assist in the early detection of AD, distinguishing it from other conditions and evaluating the effectiveness of treatments. This has the potential to significantly transform the way AD is managed clinically. By providing insights into the molecular changes that occur in the brain during the course of the disease, neuroimaging can facilitate early diagnosis, monitor disease progression, and inform treatment decisions. Furthermore, neuroimaging holds great potential for accelerating drug development by allowing researchers to assess the efficacy of novel therapies in real time. Overall, the integration of neuroimaging into the clinical management of AD has the potential to revolutionize the way we approach diagnosis, treatment, and research in AD.